Capital Structure Is the Main Consideration of Investors in the Retail Business Sector - Isman Isman; Andrijani Sumarahinsih; Khoirul Bahriyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study comprehensively investigates the empirical impact of capital structure, profitability, and asset growth on the value of companies in the retail sector on the Indonesia Stock Exchange during the post-pandemic economic recovery phase (2021–2024). Adopting a quantitative methodology with purposive sampling of 12 entities (N=48), parameters were estimated using multiple linear regression after passing a rigorous classical assumption test including normality, multicollinearity, and heteroscedasticity. By proxiesizing the capital structure through Debt to Equity Ratio (DER), profitability through Return on Assets (ROA), and total asset growth to Price to Book Value (PBV), this study reveals the phenomenon of market undervaluation with an average PBV of 0.17. The results of statistical tests confirm that these financial determinants partially and simultaneously have a significant influence on shaping the firm value. These findings provide a theoretical contribution regarding the relevance of funding policy and operational efficiency as crucial signals for investors in a volatile market landscape. The practical implications emphasize the importance of optimizing financial structure and operational performance to strengthen market confidence during the global economic transition period.